Działalność opozycyjna studentek z duszpasterstwa akademickiego i NZS w Białymstoku na przełomie lat siedemdziesiątych i osiemdziesiątych XX wieku - Kozak, Marek (Komunizm: System - Ludzie - Dokumentacja, 2023)
Students were active in the anti-communist opposition. At the end of the 1970s and the beginning of the 1980s, their activities focused on the academic ministry and the NZS. Women also play edan important role in this. The article presents the attitudes of female students during the birth of “Solidarność” and during the martial law period. The students took part in anti-communist demonstrations, in the distribution of illegal publications and were accused in the famous “Proces 21” in the Białystok region. More over, they were under the supervision of the communist repression apparatus.